Judge's Ruling in Wanprestation Lawsuit - Reyhan Agusta; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2023)
In life in society, problems related to non-performance in an agreement often occur in society. The research method used is a normative juridical approach. The difference between this article and the previous article is the different research objects, as well as using court decisions from different locations. The judge's considerations in deciding the case Sukoharjo District Court Decision No. 81/pdt.G/2022/PN.Skh, and Yogyakarta District Court Decision No. 120/Pdt.G/2022/PN.Yyk has something in common, namely that the judges both decided to grant it in part.